The Occurrence of Lithic Raw Materials in the Western Part of Central Germany. (21st January 2022) - Hess, Thomas; Riede, Felix
Due to its geological and geomorphological features, Central Germany is extremely diverse in terms of the occurrence of lithic raw materials. Based on macroscopic criteria alone, it remains challenging to unambiguously distinguish different rock types that were used for the production of stone tools in prehistoric times. Yet, only a few studies have presented a systematic description of the materials in question, including petrographic analysis. The following article presents the results of a research project, aimed at investigating the abundance of lithic raw materials in the Federal State of Hesse and adjacent regions. In the framework of field surveys, several outcrops in the study area were sampled in order to create a reference collection. These materials were analyzed and described petrographically, using optical microscopy. In combination with GIS-analysis, the results offer a robust starting point for the study of prehistoric mobility patterns and give new insights into the genesis of the various raw materials in the study area.